A Transitivity Analysis of the Arab Revolutions Representation in Western Newspapers: the Washington Post, the Guardian and le Figaro as Case Study. - Edouihri, aymane; Yahya yachouti (International Journal of Language and Literary Studies, 2020)
The earthshaking event of the Arab revolutions profoundly impacted international relations and sparked heated discussions and analysis of East and West encounters´ legacy. Such sizable opportunity is creates an interesting momentum in revisiting western representation of the orient. Such representation traditionally feeds on colonial discourse´s binarisms, polarization and othering. Thus, this paper aims at examining western press discourse on the Arab Spring through transitivity analysis. The analysis examines the Washington Post, the Guradian and le Figaro´s articles written about the Arab revolutions. Enlightened by Systemic Functional Linguistics, transitivity analysis unveils the embedded constructs in the process types, goals and actors deployed by the newspapers´ articles writers.